Extracorporeal membrane oxygenation treatment for severe asthma had unexpected adverse effects: a case report - Wang, Yun; Zhang, Weimin; Chen, Xingxing; Cheng, Xuping; Jiang, Xuandong (Frontiers in Medicine, 2023)
Asthma, a chronic respiratory ailment, affects millions worldwide. Extracorporeal membrane oxygenation (ECMO) has gained traction as a life-saving intervention for patients with severe asthma who are unresponsive to conventional treatments. However, complications associated with ECMO, including electrolyte imbalances and hemorrhage, can have significant clinical implications. This case report highlights a 49 years-old male patient with severe asthma who developed pronounced hypokalemia and hemorrhage following venovenous ECMO (VVECMO) therapy. Despite potassium supplementation, serum potassium levels continued declining before normalizing after 24 h. The patient subsequently experienced gastrointestinal bleeding, cerebral hemorrhage, and extensive cerebral infarction, ultimately resulting in a deep coma. Hypokalemia during ECMO therapy can result from a rapid reduction of carbon dioxide, β-receptor agonist use, corticosteroid use, and diuretic administration. Hemorrhage is another common ECMO complication, often linked to heparin anticoagulation therapy. Clinicians should be aware of potential complications and adopt appropriate prevention and management strategies when using ECMO in patients with severe asthma.